2019
DOI: 10.1002/asl.898
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prediction of equatorial Atlantic sea surface temperature using simple initialization and bias correction techniques

Abstract: Due to strong mean state‐biases most coupled models are unable to simulate equatorial Atlantic variability. Here, we use the Kiel Climate Model to assess the impact of bias reduction on the seasonal prediction of equatorial Atlantic sea surface temperature (SST). We compare a standard experiment (STD) with an experiment that employs surface heat flux correction to reduce the SST bias (FLX) and, in addition, apply a correction for initial errors in SST. Initial conditions for both experiments are generated in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Here we investigate this issue for the tropical Atlantic, because this is a region where current models exhibit large biases compared to the amplitude of interannual variability and have demonstrated low prediction skill. Furthermore, several previous studies have reported an influence of model biases on the simulated variability and prediction skill in this region (Ding et al 2015a;Dippe et al 2018Dippe et al , 2019.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Here we investigate this issue for the tropical Atlantic, because this is a region where current models exhibit large biases compared to the amplitude of interannual variability and have demonstrated low prediction skill. Furthermore, several previous studies have reported an influence of model biases on the simulated variability and prediction skill in this region (Ding et al 2015a;Dippe et al 2018Dippe et al , 2019.…”
Section: Discussionmentioning
confidence: 90%
“…These biases cause an underestimation of the thermocline feedback (Deppenmeier et al 2016) and an overestimation of thermodynamic ocean-atmosphere interaction (Jouanno et al 2017); and reducing them enhances the simulation of dynamical ocean-atmosphere interaction and Atlantic Niño variability (Ding et al 2015a, b;Dippe et al 2018;Harlaß et al 2018). Furthermore, Dippe et al (2019) show that reducing this bias improves the prediction of Atlantic Niño variability, although prediction skill remains poor-i.e. only beating marginally persistence for May start and beating persistence by 0.1 for August start up to 4 lead month.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…(2012): higher potential predictive skill in the tropical Pacific SST anomalies is found in the west in our ATL run (Table 2 and Figure S3) but in the east in the pacemaker experiment (Figure 4 in their paper). This discrepancy provides another perspective on the predictability that involves ENSO diversity (Capotondi et al., 2015), which might be modulated by Atlantic mean state biases, model systematic errors, and assimilation methods (Ding, Keenlyside, et al., 2015; Ding, Greatbatch, et al., 2015; Dippe et al., 2019; Johnson et al., 2020). According to previous studies (Ham, Kug, Park, & Jin, 2013; Ham, Kug, & Park, 2013), the boreal summer Atlantic Niño enhances occurrences in the eastern Pacific type of ENSO in the subsequent winter, whereas the spring North Atlantic SST anomalies contribute to an increase in the central Pacific type of ENSO events.…”
Section: Discussionmentioning
confidence: 99%
“…• Skill of monthly ENSO hindcasts Smith et al, 2013;Vecchi et al, 2014;Ding et al, 2015;Kim et al, 2017;Scaife et al, 2019;Dippe et al, 2019). For example, Manganello and Huang (2009) found that a CGCM warm SST bias off the South American coast degrades ENSO forecast skill.…”
Section: 1029/2019gl086765mentioning
confidence: 99%